2012
DOI: 10.3402/ljm.v7i0.19852
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiumin countries of the Arab world: the past decade (2002–2011)

Abstract: Introduction Cryptosporidium is the causative agent of cryptosporidiosis. The disease is self-limited in immunocompetent persons but potentially life-threatening in immunocompromised individuals.MethodsThe data included in the present review were obtained mainly from a Highwire Press (including PubMed) search for the period 2002–2011.ResultsInformation on cryptosporidiosis is lacking in some Arab countries; however available data show prevalence rates of <1–43% (mean = 8.7%) of Cryptosporidium infection in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…have been suggested to be associated with the widespread custom of employing foreign maids who usually have direct contact with children. A high prevalence (46.5%) of intestinal parasites among female Asian housekeepers in that study, suggests that members of families with foreign housekeepers may be at some risk of parasitic infections (Ghenghesh et al, 2012 ).…”
Section: Discussionmentioning
confidence: 81%
“…have been suggested to be associated with the widespread custom of employing foreign maids who usually have direct contact with children. A high prevalence (46.5%) of intestinal parasites among female Asian housekeepers in that study, suggests that members of families with foreign housekeepers may be at some risk of parasitic infections (Ghenghesh et al, 2012 ).…”
Section: Discussionmentioning
confidence: 81%
“…The trend of increased prevalence rate of cryptosporidiosis in children from urban to suburban and rural areas was also observed in Yemen [41]. A review of publications of cryptosporidiosis (between 2002 and 2011) in Arabic countries indicated Cryptosporidium species infection among pediatrics in rural and semiurban areas was higher than in urban areas [42]. Results of our study showed that the prevalence of Cryptosporidium in children hospitalized in suburb hospitals (7.8%) was significantly higher Table 4: Comparison of 18S rRNA gene sequence of Cryptosporidium from children hospitalized for diarrhea in Guangzhou to highly related sequences of Cryptosporidium in the GenBank (BLAST analysis conducted on January 23, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Similar results have also been reported in previous studies from other countries. In countries of the Arab world, higher prevalences of Cryptosporidium were found in children living in rural and semi-urban areas than in those residing in urban areas during the decade from 2002 to 2011 [55]. In a retrospective analysis of human cryptosporidiosis cases conducted in New Zealand from 2004 to 2011, the prevalence of cryptosporidiosis in rural areas (yearly average of 71.5 cases per 100,000; 95% confidence interval (CI) 64.6-78.3) was observed to be more than twice that of urban areas (yearly average of 29.2 cases per 100,000; 95% CI 26.9-31.5) [56].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%